HUMAN IMPACT ON KUTTANAD WETLAND ECOSYSTEM - AN OVERVIEW - K.A. Sreejith (International Journal of Science, Environment and Technology, 2013)
Kuttanad is one among the unique wetland ecosystem in the country where human impact is severe which alter the structure, function, composition and services of the ecosystem. This study focusing on the threats to the ecosystem, especially due to anthropogenic activities, its causes and possible solutions. The study also analyses the history of human activities and its impact on this ecosystem and immediate steps to undertake to restore this human impacted landscape. The review clearly indicates that the man-made activities altered the ecosystem drastically and it is high time to act on it otherwise the unique ecosystem may loss its entire beauty and ecological significance and an immediate mass level eco-restoration programme is suggested. Proper implementation and monitoring of Kuttanad Package may do it for time-being. Since this package is a time bound one, a permanent long- term programme has to be developed and implemented to conserve this ecosystem.